An analysis of the language of communication used by Barclays Bank Zimbabwe - Mushore, Washington (Not Known, 2016)
An advertisement, according to Larson (2001), carries a lot of meaning, “signified” by the verbal and nonverbal symbols being used (or perhaps misused depending on one’s perspective). The aim of advertising is to tell potential clients or customers about the products, services or ideas of an organisation and then try to sell those products, services and ideas to them. Moreover, when advertising, organisations endeavour to communicate certain positive aspects or traits of their products, services or ideas to potential customers or clients. Banks in Zimbabwe are currently competing in an environment characterised by a limited and diverse number of potential clients owing to the harsh political and economic environment. This has culminated in some company closures. Using semiotic analysis, this article therefore argues that the languages (colours, words, images and font types and sizes) advertisers use in such an environment in their advertisements is not by accident but by design. These languages are skilfully and thoroughly programmed so that they cajole or tantalize the targeted clients to think, react and behave in certain predetermined ways. In order to support the above mentioned argument, Barclays Bank Zimbabwe advertisement will be used as an example.